Edith Stein e as questões de gênero: perspectiva fenomenológica e teológica - Peretti, Clélia (2009)
This thesis discusses the issue of gender, a major issue for our time. It aims to analyze the phenomenological and theological perspective of gender issue in the contributions of Edith Stein (1891-1942), philosopher and disciple of Edmund Husserl (1859-1938). Therefore, examines the relationship between male and female, highlighting mainly the women's issues. This study emphasizes also the presence of Edith Stein in the women's literature of the time, their participation in educational and feminist movements, its relevance in the phenomenological school ability to move in different areas of knowledge and its applicability of the original phenomenological method in the study of the human person in its various dimensions: body, soul, spirit, values, relationship with others and with God. Edith Stein is concentrated around the subject of empathy and their experiences. The analysis of interpersonal relations collects information for the elaboration of a philosophical anthropology that the meeting with the Aristotelian- Thomistic tradition integrates with Christian anthropology. Throughout the work, it is being seek an exam of the relationship between human beings and the religious dimension, with particular reference to Catholic theology. It discusses the meanings of the ontological nature and essence of the woman suggested by the philosopher in a complementary prospective. The research deals with contemporary women's issue and makes comparison between the writings of Edith Stein and status of women in her time. At the same time, addresses the feminist movement in Brazil to demonstrate the situation of women in different historical and social contexts. From the theological point of view, the relationship between man and woman is studied in the light of Judeo- Christian Revelation, man and woman created in the image of God and the Trinity. The woman wins her nobility because of the Redeemer to be born from a human mother; Mary is presented as a prototype of femininity: the Mater-Virgo and Sponsa-Christi. In this regard, the reference is made to the Christian tradition, particularly to the Apostolic Letter Mulieris Dignitatem from John Paul II. It demonstrates the close relationship between the anthropological and philosophical reflections of philosophers on the theology of femininity in the Catholic Church and the proposal of a new feminism of the Church. This thesis also reflects on the role of women, from the fundamental value of human male and female. It tries to allude to the Christian religious as an opening and meeting experience of the Revelation, individual and collective journey. Finally, it waves to the phenomenology of spirituality and mystical theology in detail by Edith Stein, inspired by the works of St. Teresa of Avila and St. John of the Cross.